Earthquakes and eschatology in the gospel according to Matthew - Carrier, Brian 1981-; Catholic University of America; Mohr Siebeck GmbH & Co. KG (Tübingen Mohr Siebeck, 2020)
Cover -- Title -- Preface -- Table of Contents -- List of Tables -- Chapter 1: Introduction -- A. Purpose and Justification -- B. Scope and Structure -- C. State of Research on Matthean Seismology -- D. Methodology -- E. Summary -- Chapter 2: Matthew's Encyclopedia of Production -- A. The Old Testament -- I. Earthquakes -- 1. Theophany -- 2. Excursus: The Day of the Lord -- 3. Non-Theophanic Divine Activity -- II. Anthropological Shaking -- III. Other Shaking -- IV. Deuterocanonical Books -- V. Summary -- B. Early Jewish Literature -- I. Pseudepigrapha -- II. Qumran -- III. Josephus -- IV. Philo -- C. Early Christian Literature -- I. The New Testament -- II. Apostolic Fathers -- D. Greco-Roman Literature -- E. Conclusion -- Chapter 3: The σεισμός at Sea -- A. Engaging the Majority Position -- B. Resetting the Context -- I. The Kingdom of Heaven -- II. The Kingdom of Heaven in Matthew 5-9 -- III. The Kingdom of Heaven in Matthew 1-4 -- IV. The Kingdom of Heaven in Matt 8:23-27 -- C. The σεισμός of Matt 8:24 -- I. Epiphanic Resonance -- II. Eschatological Resonance -- III. The Matt 8:24 @@as an Epiphanic and Eschatological Indicator -- D. Conclusion -- Chapter 4: Shaken, and Stirred -- A. Setting the Context -- I. The Return of the King -- II. The Contrast in Reception -- III. The Characterization of Jerusalem -- IV. The Arrival of Judgment -- V. Jerusalem's Day of the Lord -- B. The Shaking of Jerusalem -- C. Conclusion -- Chapter 5: The σεισμός at the Cross -- A. Setting the Context -- I. The Cross as Christological Validation -- II. The Cross as Eschatological Divine Intervention -- 1. Divine Salvation -- 2. Resurrection of the Dead -- 3. Victory over Death and Evil -- 4. Gentile Conversion -- 5. Restoration of the Human-Divine Relationship -- 6. The Temple's Destruction -- 7. Divine Judgment -- III. Summary -- B. The Earthquake at Calvary.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books; Hochschulschrift